Effect of Cognitive Behavior Therapy (CBT) Intervention on Serum Cortisol Level and Pain Score of Patients with Advanced-Stage Cervical Cancer - . Soetrisno; Sri Sulistyowati; Supriyadi Hari Respati; Rizka Pramudhita (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
ABSTRACTCervical cancer is the most frequent cause of death related gynecology malignancy in Indonesia. Recent management of advanced-stage cervical cancer has still not been able to improve the prognosis. Chemotherapy and radiation intervention, as well as therapy may resulting pain and cause psychological stress for some patient, furthermore it could effect on the quality of life. Cortisol is a hormone of adrenal cortex, it secretes due to increased production of ACTH by anterior pituitary which is associated with stressful condition. To analyze the effect of Cognitive Behavior Therapy (CBT) intervention on serum cortisol levels and pain score of patients with advanced-stage cervical cancer. This experimental study was a double blind non-randomized clinical trial post-test group design. It was using two groups in this study, each group consisting of 15 subjects, the treatment group were given CBT and standard therapy, while the control group were only given a standard therapy. The study was conducted in the gynecology oncology ward and the gynecology oncology clinic of Dr. Moewardi Hospital Surakarta and Prodia Laboratory, from January - March 2015. Cortisol level of the treatment group was 1.03 ± 0.71 mg / dL, and the control group was 11.41 ± 7.34 mg / dL. Pain score in the treatment group was 4.46 ± 0.83, and the control group was 7.34 ± 0.74. There are significant differences in serum cortisol level decrease (p = 0.00) and pain score (p = 0.00) between the CBT intervention with standard therapy group compared and the standard therapy only group